Interaction of short-term copper pollution and ocean acidification in seagrass ecosystems: Toxicity, bioconcentration and dietary transfer. (May 2019) - de los Santos, Carmen B.; Arenas, Francisco; Neuparth, Teresa; Santos, Miguel M.
Abstract: We aimed to show how the predicted pH decrease in the ocean would alter the toxicity, bioconcentration and dietary transfer of trace metal copper on seagrass ecosystems, on a short-term basis. Seagrass Zostera noltei was exposed to two pH levels (8.36 and 8.03) and three copper levels (nominal concentrations, <3, 30 and 300 μg Cu L −1 ) in a factorial design during 21 days, while Gammarus locusta amphipods were continuously fed with the treated seagrass leaves. We found that the toxicity and bioconcentration of copper in seagrasses were not affected by pH, yet complex copper-pH interactions were observed in the seagrass photosynthesis. We demostrated that seagrasses can act as a copper source in the food web via direct consumption by herbivores. Future research need to investigate the interactive effects on a long-term basis, and to include biochemical and molecular endpoints to provide additional insights to the complex phisiological interactions observed. Highlights: Toxicity and bioconcentration of copper in seagrasses were not affected by pH. Complex copper-pH interactions were observed in the seagrass photosynthesis. Seagrasses can act as a copper source in the food web via direct consumption.